1987
DOI: 10.1007/bf01907227
|View full text |Cite
|
Sign up to set email alerts
|

Prostacyclin and iloprost: Equal efficiency in preserving high energy phosphates in the dog heart following coronary artery ligation

Abstract: The influence of PGI2 and iloprost on the contents of high energy phosphates, cAMP, glycolytic metabolites and on cardiac performance was investigated in open-chest dogs subjected to 3 h of ischaemia, induced by occlusion of the left anterior descending coronary artery. The administration of drugs for 2 h, starting 1 h after the onset of ischaemia, resulted in a normalization and an appreciable reduction in the loss of high energy phosphates in the non-ischaemic and ischaemic left ventricular muscle, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Inhibition of thromboxane A2 production or blocking its receptor during ischaemia has been demonstrated to protect the myocardium against ischaemia/reperfusion injury as evidenced by prevention of an increase in lactate release from the heart, limitation of cardiac risk area and decrease in reperfusion-induced arrhythmias (Sakai et al, 1982;Thiemermann & Schrbr, 1984;Grover et al, 1988;1990;Mehta et al, 1990;Lesenefsky et al, 1990). Furthermore, several investigators have found that treatment with iloprost, a prostacyclinmimetic agent, improved myocardial metabolism during ischaemia and resulted in an enhanced recovery of cardiac function (Van Glist et al, 1983;Giessen et al, 1986;Pissarek et al, 1987;Chiariello et al, 1988;Ferrari et al, 1988). These results suggest an involvement of prostacyclin-mimetics in the enhancement of post-hypoxic or post-ischaemic functional and metabolic improvement of the myocardium.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Inhibition of thromboxane A2 production or blocking its receptor during ischaemia has been demonstrated to protect the myocardium against ischaemia/reperfusion injury as evidenced by prevention of an increase in lactate release from the heart, limitation of cardiac risk area and decrease in reperfusion-induced arrhythmias (Sakai et al, 1982;Thiemermann & Schrbr, 1984;Grover et al, 1988;1990;Mehta et al, 1990;Lesenefsky et al, 1990). Furthermore, several investigators have found that treatment with iloprost, a prostacyclinmimetic agent, improved myocardial metabolism during ischaemia and resulted in an enhanced recovery of cardiac function (Van Glist et al, 1983;Giessen et al, 1986;Pissarek et al, 1987;Chiariello et al, 1988;Ferrari et al, 1988). These results suggest an involvement of prostacyclin-mimetics in the enhancement of post-hypoxic or post-ischaemic functional and metabolic improvement of the myocardium.…”
Section: Discussionmentioning
confidence: 95%
“…Since these agents decrease energy demand during hypoxia or ischaemia by suppression of cardiac contractility, they protect the myocardium from depletion of high-energy phosphate levels, that is, they have an energy sparing effect (Nayler et al, 1978). Prostacyclin and iloprost have been shown to preserve high-energy phosphates in the heart following coronary artery ligation (Pissarek et al, 1987). Thus, it is conceivable that prostacyclin and its mimetic agent have an energy-sparing effect on hypoxic or ischaemic myocardium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extract preparation. The extract was prepared as previously described (Pissarek et al 1987). The slices were homogenized under addition of 0.5 M perchloric acid in a mortar cooled with liquid nitrogen.…”
Section: Biochemical Experimentsmentioning
confidence: 99%